(untitled) (Fiep Bulletin - online, 2015)
Vertigo is a term that genetically represents all sensations of dizziness. Dizziness is among the most frequent symptoms and is the origin of Labyrinth in 85% of the cases. The current study objective was to verify the efficacy of vestibular rehabilitation people suffering from benign paroxysmal positional vertigo (BPPV). In a clinic specialized in the otorhinolaryngologist area in the city of Cascavel, Paraná, Brazil, six male and female patients with a medical diagnose and prescribed medicine, age 40 to 85, were selected. All patients were submitted to a initial, intermediate, and final evaluation previously elaborated through Jacobson & Newman’s Dizziness Handicap Inventory School. Patient’s physical, emotional, and functional improvement were verified. Three patients performed Cawthorne-Cooksy’s physical treatment protocol, and the other three patients participated in the control group. Patients were examined three times a week, for a period of thirty minutes in each visit, totaling ten examinations. The results obtained from the patients that underwent the treatment were extremely satisfactory obtaining an improvement that varied from 91.69% to 96.19%. The results point vestibular rehabilitation as a valid option for the treatment of benign paroxysmal positional vertigo.